Fraud Hexagon Analyzer: an excel-powered risk indicator - Saidi, Noraida; Mohamad, Amri; Nik Abdul Majid, Wan Zurina (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
Financial reporting fraud (FFR) continues to be a widespread concern to organisations, resulting in significant financial losses, reputational harm, and reduced stakeholder confidence. Current fraud detection techniques are typically reactive, limited by poor datasets, and inadequate for tackling the evolving nature of fraud. This project aims to fill a significant gap by introducing a Fraud Hexagon Analyser based on the Fraud Hexagon framework, a comprehensive model by integrating six essential elements: pressure, opportunity, rationalisation, capability, arrogance and collusion. This innovation project utilises an interactive Excel dashboard combined with predictive analytics and Fraud Hexagon concepts to provide a user-friendly, scalable, and economical fraud risk assessment solution. The dashboard provides users with the ability to visualize and analyze fraud risk indicators in real time by taking data from annual reports and looking to visualize it through the data visualization, automated risk assessment and notification settings to assist the user to quickly discover and prioritize flaws, it is user friendly, and it is available to public listed companies in Malaysia with publicly available annul reports. The originality of this approach lies in the use of the Fraud Hexagon through user friendly and available tools like Excel, therefore leaving it largely dependent upon the will of the user to satisfy easy and satisfactory implementation at low costs. The dashboard buys into how traditional fraud detection functions conduct fraud detection because they direct all their effort into investigation after an incident; it can identify risk trends and anomalies and is proactive in nature which should help organizations create supportable preventive actions. Public listed companies as potential users of the tool may receive many benefits as it would be inexpensive, only requiring adaptation to their particular needs to effectively use it, and would provide lots of practical, actionable material to help them to mitigate fraud without an abundance of technical capabilities involved. This project fills an important role of a considerable absence of these tools in the fraud prevention toolbox applying the Fraud Hexagon framework to provide by using an innovative approach to Excel. The proposed tool is innovative, accessible, and strategic, thereby it is also potentially, evaluative therefore ensuring the commercial viability of the tool, while also ensuring social and economic benefits.